Explaining an Adoption and Continuance Intention to Use Contactless Payment Technologies: During the COVID-19 Pandemic - Wilert Puriwat; Suchart Tripopsakul (Ital Publication, 2021)
The COVID-19 pandemic has affected the lives of people and services, pushing them toward new technologies that are in step with the development of a “New Normal” way of life. Contactless technologies have been realized as a mechanism to reduce the risks of infection, accelerating the move to touchless behaviors. The purpose of this study is to develop an Integrated Expectation-Confirmation and Health Belief Model (ECHBM) to explain an adoption and continuance intention to use contactless technologies during the COVID-19 pandemic in Thailand. Based on an empirical research survey of 142 samples, the proposed conceptual model was empirically validated using structural equation modelling (SEM). The study found that perceived usefulness, perceived susceptibility, perceived seriousness, and satisfaction significantly influenced continuance usage intention of contactless payment technologies, whereas perceived usefulness and confirmation were found to be significant determinants of consumer satisfaction. The effect of perceived susceptibility was found to be relatively higher than that of satisfaction, and confirmation was found to have an indirect effect on continuance usage intention through perceived usefulness and satisfaction. The integrated ECHBM model has strong explanatory power (56.8%) to predict customers’ continuance usage intention toward use of contactless payment technologies during the COVID-19 pandemic. The study proposes a novel challenge to explain an adoption and continuance intention to use contactless payment technologies as a protective health behavior to mitigate risks of being infected by COVID-19. Doi: 10.28991/esj-2021-01260 Full Text: PDF